Platform proliferation and its implications for domestic content policies. Issue 2 (May 2016) - Picard, Robert G.; Davis, Charles H.; Papandrea, Franco; Park, Sora
Abstract: The rapid rise in audio-visual distribution platforms is challenging regulators' abilities to fashion and maintain domestic content policies designed to support national production and national cultural protection and promotion objectives. Broadcasters in a number of nations and regions operate under content regulatory schemes designed to serve cultural and economic purposes, put into place during the age of terrestrial broadcasting in which national policymakers could tightly control the availability of content in the country. This article explores these issues through an analysis of the rationales, policy approaches, and effectiveness of domestic content policies in four countries (Australia, Canada, Ireland, and South Korea) and considers the implications of these approaches in a globally connected environment. The researchers identified common issues across the four countries: (1) development of national content industries does not necessarily imply the promotion or protection of national culture, (2) production companies and broadcasters have interests and incentives that diverge from those of policymakers, and (3) it is difficult to assess the relevance and quality of broadcast content with regards to domestic culture other than in terms of conventional standards: critical acclaim and audience share.